Kidney Diseases Caused by Complement Dysregulation: Acquired, Inherited, and Still More to Come - Saskia F. Heeringa; Clemens D. Cohen (Clinical and Developmental Immunology)
Inherited and acquired dysregulation of the complement alternative pathway plays an important role in multiple renal diseases. In recent years, the identification of disease-causing mutations and genetic variants in complement regulatory proteins has contributed significantly to our knowledge of the pathogenesis of complement associated glomerulopathies. In these diseases defective complement control leading to the deposition of activated complement products plays a key role. Consequently, complement-related glomerulopathies characterized by glomerular complement component 3 (C3) deposition in the absence of local immunoglobulin deposits are now collectively described by the term “C3 glomerulopathies.” Therapeutic strategies for reestablishing complement regulation by either complement blockade with the anti-C5 monoclonal antibody eculizumab or plasma substitution have been successful in several cases of C3 glomerulopathies. However, further elucidation of the underlying defects in the alternative complement pathway is awaited to develop pathogenesis-specific therapies.